2020
DOI: 10.1002/1878-0261.12761
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of therapy‐induced senescent tumor cells by the senolytic ABT‐263 via interference with BCL‐XL–BAX interaction

Abstract: Tumor cells undergo senescence in response to both conventional and targeted cancer therapies. The induction of senescence in response to cancer therapy can contribute to unfavorable patient outcomes, potentially including disease relapse. This possibiliy is supported by our findings that tumor cells induced into senescence by doxorubicin or etoposide can give rise to viable tumors in vivo. We further demonstrate sensitivity of these senescent tumor cells to the senolytic ABT-263 (navitoclax), therefore provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 76 publications
11
81
0
Order By: Relevance
“…Clearance of senescent tumor cells by navitoclax has been reported to enhance tumor regression/control and increase mouse survival [27,50,143]. As in non-tumor models, the senolytic activity of ABT-263 appears to depend upon inhibition of BCL-X L [27,50]. Further, our laboratory has recently reported that BAX, but not BAK, is required for cell killing by ABT-263 [27].…”
Section: Early Evidence On Senolytics As Anti-cancer Therapiesmentioning
confidence: 97%
See 4 more Smart Citations
“…Clearance of senescent tumor cells by navitoclax has been reported to enhance tumor regression/control and increase mouse survival [27,50,143]. As in non-tumor models, the senolytic activity of ABT-263 appears to depend upon inhibition of BCL-X L [27,50]. Further, our laboratory has recently reported that BAX, but not BAK, is required for cell killing by ABT-263 [27].…”
Section: Early Evidence On Senolytics As Anti-cancer Therapiesmentioning
confidence: 97%
“…As in non-tumor models, the senolytic activity of ABT-263 appears to depend upon inhibition of BCL-X L [27,50]. Further, our laboratory has recently reported that BAX, but not BAK, is required for cell killing by ABT-263 [27]. However, in a recent publication with irradiated soft-tissue sarcoma, BCL-2 inhibition, albeit using supraclinical concentrations of ABT-199, was sufficient to promote senolysis, demonstrating the complex heterogeneity in which BCL-2 family member proteins senescent tumor cells depend upon for survival [146].…”
Section: Early Evidence On Senolytics As Anti-cancer Therapiesmentioning
confidence: 99%
See 3 more Smart Citations